A Review of an Underutilized Legume Canavalia gladiata - Ekanayake, Sagarika; Jansz, E.R.; Nair, Baboo M.; Abeysekera, A.M. (My University, 1999)
The literature related to the legume commonly known as sword beans (Canavalia gladiata) that belongs to the genus Canavalia which is considered to be an underutilized legume, is reviewed. The legume seeds are considered to be a cheap source of good protein and calories that are easily available. However, even with this knowledge, the utilization of most legumes is apparently low. Sword beans have favorable agronomic features suitable for cultivation in the tropics and a high average yield comparable to that of soybeans. The agroclimatic conditions suitable for cultivation, morphological features, uses, chemical composition and the antinutritional factors of the plant are discussed.